The flattened seabed characters at the nearshore islands of Vietnam - Tuan, Tong Phuc; Thinh, Vo; Khanh, Uong Dinh; Dung, Bui Quang; Dung, Chu Anh (Vietnam Journal of Marine Science and Technology, 2020)
Flattened seabed characters at the nearshore islands, namely Bach Long Vi, Con Co, Ly Son, Phu Quy, Hon Khoai and Tho Chu, were analysed based on depth contour map with 1 m vertical resolution and the application of ArcMap 10.4 software. Consequently, a series of seabed cross sections was automatically created by using the software, which provides the time-saving benefit and improves the scientific relevance. The result shows that flattened seabed characters of those islands were comparable in terms of general pattern, but still remained some distinctions depending on particular location. The depth of flattened seabed levels does not reach 30–50 m depth at northern and southern Vietnam’s sea (seabed surrounding Bach Long Vi, Hon Khoai, Tho Chu islands), while the value reaches over 100 m depth at southern central Vietnam’s sea (seabed surrounding Ly Son, Phu Quy islands). The classification of flattened seabed reveals the following depth levels: 0–2 m, 5–8 m, 12–14 m, 20–25 m, 25–27 m, 27–30 m, 32–35 m, 40–45 m, 45–50 m, 53–55 m, 60–65 m, 65–70 m, 75–85 m and 90–115 m.